Coumarin accumulation and trafficking in Arabidopsis thaliana: a complex and dynamic process. Issue 4 (16th December 2020) - Robe, Kevin; Conejero, Geneviève; Gao, Fei; Lefebvre‐Legendre, Linnka; Sylvestre‐Gonon, Elodie; Rofidal, Valérie; Hem, Sonia; Rouhier, Nicolas; Barberon, Marie; Hecker, Arnaud; Gaymard, Frédéric; Izquierdo, Esther; et al.
Summary: Iron (Fe) is a major micronutrient and is required for plant growth and development. Nongrass species have evolved a reduction‐based strategy to solubilize and take up Fe. The secretion of Fe‐mobilizing coumarins (e.g. fraxetin, esculetin and sideretin) by plant roots plays an important role in this process. Although the biochemical mechanisms leading to their biosynthesis have been well described, very little is known about their cellular and subcellular localization or their mobility within plant tissues. Spectral imaging was used to monitor, in Arabidopsis thaliana, the in planta localization of Fe‐mobilizing coumarins and scopolin. Molecular, genetic and biochemical approaches were also used to investigate the dynamics of coumarin accumulation in roots. These approaches showed that root hairs play a major role in scopoletin secretion, whereas fraxetin and esculetin secretion occurs through all epidermis cells. The findings of this study also showed that the transport of coumarins from the cortex to the rhizosphere relies on the PDR9 transporter under Fe‐deficient conditions. Additional experiments support the idea that coumarins move throughout the plant body via the xylem sap and that several plant species can take up coumarins present in the surrounding media. Altogether, the data presented here demonstrate that coumarin storage and accumulation in roots is a highly complex and dynamic process.